Norwegian scabies in a resident of a nursing home misdiagnosed as dermatologic lesions of type 2 diabetes mellitus - Jacek Kasznicki; Marcin Kosmalski; Józef Drzewoski (Termedia Publishing House, 2014)
Introduction. Norwegian (crusted, hyperkeratotic) scabies is a relatively rare form of the disease, but it is highly contagious and easily transmitted. Although skin lesions are typical for that form of the disease, they differ substantially from those observed in typical infection with Sarcoptes scabiei. Objective. To present the difficulties in the diagnosis of Norwegian scabies. Case report. We describe a case of an elderly patient, a resident of a nursing home, with Norwegian scabies in whom itching and skin lesions were initially misdiagnosed as a dermatologic complication of type 2 diabetes mellitus. Additionally, in the nursing home, the results of the implemented therapy were not checked appropriately, which resulted in an outbreak of scabies in the institution as well as infection of several family members. Conclusions . Considering the fact that pharmacological treatment of Norwegian scabies does not differ from other forms of this disease, it seems that early diagnosis and appropriate treatment planning are crucial to prevent transmission of the infection.